Cause Related Marketing and Purchase Intention Consumers' Goods in Nepal - Khanal, Jayant Nath (Tribhuvan University Journal, 2013)
In an emerging market, social development is an imperative, brands, consumers and society will benefited by cause-related marketing (CRM) that could provide an avenue to those in need receive more support than can be provided by traditional means. Though considerable work on CRM campaign sand consumer responses to them have been undertaken show ever, not much research has been done in this field in Nepal. In this connection, present study attempts to examine consumer responses on CRM, and particularly investigates whether the consumers’ level of involvement with a cause and the way in which the message is framed influence purchase intention. This study reveals that cause involvement is significantly influencing factor fir purchase intention while message framing did not. Therefore, there was no interaction between cause involvement and message framing.